Master of Medicine (MMED) in Obstetrics & Gynaecology - Kabale University (Kabale University, 2022)
This programme deals with all aspects of pregnancy, including: antenatal care, normal physiology, early pregnancy problems and other pathological events which occur during pregnancy and labour. Obstetrics also involves the study of the Foetus as an individual which is intimately related to the health of the mother.